2016
DOI: 10.1111/all.12865
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between adult asthma and oxidative stress markers and pH in exhaled breath condensate: a systematic review

Abstract: Oxidative stress has a recognized role in the pathophysiology of asthma. Recently, interest has increased in the assessment of pH and airway oxidative stress markers. Collection of exhaled breath condensate (EBC) and quantification of biomarkers in breath samples can potentially indicate lung disease activity and help in the study of airway inflammation, and asthma severity. Levels of oxidative stress markers in the EBC have been systematically evaluated in children with asthma; however, there is no such syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(58 citation statements)
references
References 71 publications
(273 reference statements)
3
53
0
2
Order By: Relevance
“…11 Although many of the inflammatory markers are likely to come from the lower airways, some will also be generated from the larger and upper airways. 12 Several studies have examined the associations between oxidative stress biomarkers in EBC and asthma, 13,14 but less is known about the associations between the levels of EBC biomarkers and rhinitis. 15 Moreover, atopic sensitization is strongly associated as a prelude to the development of allergic diseases, including asthma and rhinitis, which has given rise to the concept of the "unified airway."…”
Section: Introductionmentioning
confidence: 99%
“…11 Although many of the inflammatory markers are likely to come from the lower airways, some will also be generated from the larger and upper airways. 12 Several studies have examined the associations between oxidative stress biomarkers in EBC and asthma, 13,14 but less is known about the associations between the levels of EBC biomarkers and rhinitis. 15 Moreover, atopic sensitization is strongly associated as a prelude to the development of allergic diseases, including asthma and rhinitis, which has given rise to the concept of the "unified airway."…”
Section: Introductionmentioning
confidence: 99%
“…The results were more often detected in patients with severe and uncontrolled asthma. 82 In another systematic review by Thomas et al, 46 studies were evaluated to show the relation between EBC markers and asthmatic inflammation and oxidative stress in children. The results suggested that hydrogen ions (as pH), hydrogen peroxide, and oxides of nitrogen are associated with pediatric allergic asthma and exacerbations.…”
Section: Findings In the Airways (Exhaled Breath Condensate Bronchmentioning
confidence: 99%
“…[68][69][70] A noninvasive way of analysis, exhaled breath condensate collection, has allowed direct measurements of pH changes, H 2 O 2 , and the measurement of several indirect by-products of oxidation like 8-isoprostane and ethane. 82,83 Currently, the presence of high levels of urine bromotyrosine is a promising noninvasive biomarker of oxidative stress for clinical use in asthma patients.…”
Section: B I Omark Er S For Oxidative S Tre Ss In a S Thmamentioning
confidence: 99%
“…Astım, kronik obstruktif akciğer hastalığı ve hatta akciğer neoplazilerinde EBC yöntemi ile gösterilen oksidatif stresin erken tanıda fayda sağlayabildiği belirtilmektedir (7,9,15,16). Diyabetik olgularda ise özellikle soluk havasında C-peptidin saptanması kronik inflamasyonun bir yansıması olarak yorumlanmaktadır (9,17,18).…”
Section: Sonuçunclassified